2016
DOI: 10.1371/journal.pone.0162354
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus Is Associated with More Serious Small Intestinal Mucosal Injuries

Abstract: BackgroundClinical and experimental research has revealed that diabetes mellitus (DM) is characterized by intestinal hypomotility, gut microbial dysbiosis, increased gut permeability, microcirculation disorders, circulatory changes, and dysfunction of intestinal stem cells, which may be linked to inflammation of intestinal mucosa. However, the relationship between type 2 DM (T2DM) and macroscopic small intestinal mucosal injuries is still unclear. Therefore, we retrospectively studied capsule endoscopy data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Although there were no statistically significant differences in the villi length (data not shown), we observed that the villi width was larger in the control yogurt-fed mice compared to the milk- and synbiotic yogurt-fed groups ( Figure 4 a,b). Because wider villi may be a sign of swelling or inflammation [ 22 ], our results suggest that the intestine of mice fed the control yogurt may have had higher levels of inflammation. Interestingly, the expression of barrier function proteins, such as tight junction protein-1 (Tjp-1)/Zonulin-1 and occludin-1 (Ocln1), were significantly higher in the ileum of synbiotic-yogurt fed mice compared to the milk- and control yogurt-fed groups ( Figure 4 c,d).…”
Section: Resultsmentioning
confidence: 99%
“…Although there were no statistically significant differences in the villi length (data not shown), we observed that the villi width was larger in the control yogurt-fed mice compared to the milk- and synbiotic yogurt-fed groups ( Figure 4 a,b). Because wider villi may be a sign of swelling or inflammation [ 22 ], our results suggest that the intestine of mice fed the control yogurt may have had higher levels of inflammation. Interestingly, the expression of barrier function proteins, such as tight junction protein-1 (Tjp-1)/Zonulin-1 and occludin-1 (Ocln1), were significantly higher in the ileum of synbiotic-yogurt fed mice compared to the milk- and control yogurt-fed groups ( Figure 4 c,d).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SCFA is a nutrient source for enterocytes and promotes gut barrier function [10][11][12][13]. Accordingly, patients with T2D show increased gut permeability and signs of intestinal injury [14][15][16][17]. Lipopolysaccharide (LPS) can translocate through the damaged gut barrier, act as a potent inflammatory mediator, influence insulin sensitivity and disturb the functionality of the innate immune system [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The present patient had poorly controlled type 2 diabetes, a proinflammatory state characterized by increased levels of C-reactive protein and proinflammatory cytokines as well as monocyte activation ( 15 ). In addition to inflammatory bowel diseases, studies have shown that patients with diabetes exhibit digestive tract inflammation and increased intestinal vulnerability ( 16 , 17 ). Mucosal vulnerability associated with diabetes may have contributed to the rectal injury following forcible insertion, which then promoted the glycerol-induced hemolysis in the present case.…”
Section: Discussionmentioning
confidence: 99%